(untitled) (Development Service Industry Management, 2024)
Compliance with safety rules in accommodation facilities is not only for customers, but also for employees, as creating appropriate protection conditions is based on the full implementation of occupational safety and health rules, and thus on fostering a “safety culture”. To achieve a high level of security, it is necessary to use tools and knowledge to deal with various security scenarios. The ability to use security protocols in accommodation facilities increases the ability to protect yourself, your colleagues and, most importantly, hotel guests. Early detection of potential threats in the security system prevents accidents, legal problems, saves money and increases the credibility of the hotel company in the long run. The use of effective security systems for accommodation facilities plays a key role in improving the quality of hotel services and employee and customer satisfaction. Methods to ensure the safety of hotel staff include regular training and education on occupational safety and health, implementation of modern security systems, such as video surveillance, use of geolocation-based panic buttons with a system of location sensors, creation of an up-to-date incident reporting system, verification of identifiers (IDs, identity documents), and instructions on the rational distribution of physical activity. However, to measure security quality, hotels must track key performance indicators such as the number of incidents, compliance with security protocols, and staff and guest satisfaction.